The changing face of trauma, head and neck injuries resulting from interpersonal violence in Johannesburg - Gersun, Dean (My University, 2019)
Background: Trauma and intentional injury form a major burden of disease in South Africa. The rates of Interpersonal Violence (IPV) in South Africa are five times higher than the global average. The face, head and neck are often the primary site of injury resulting from IPV, due to their lack of protection and these injuries are associated with considerable morbidity and mortality. Objective: The objective of this study was to examine examines the changing patterns of injury to the head and neck, resulting from IPV in patients presenting at a Level One trauma centre serving an urban population over 5 years. Data was collected of patients attending the Johannesburg Hospital Trauma Unit, over a period of 40 consecutive days (26 July – 4 September) in 2007 and 2012. The data was collected in two separate periods of 40 consecutive days on the exact same calendar dates, five years apart, initially in 2007 and subsequently in 2012. Methods: Data was collected of patients attending the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) Trauma Unit, over a period of 40 consecutive days (26 July – 4 September) in 2007 and 2012. Data from patients with injuries to the head and neck as a result of IPV were extracted and a cross-sectional analysis was performed. A secondary data analysis was performed on the existing data set from these two separate periods. Results: A total of 498 patients in 2007 and 372 patients in 2012 presented with IPV injuries over the same 40-day period. In 2007, 43% (n=212) of patients had injuries to the head and neck compared to 49% in 2012 (n=181). The median age was 28 years (23-33) in 2007 and 27 years (24-33) in 2012 with males making up 86% (n=183) and 83% (n=151) of the total respectively. There were significantly more minor injuries (swellings, lacerations; tangential gunshot wounds (GSW) and closed fractures) compared to major injuries in 2012 (p=0.02). Injuries from knives and bottles were similar in both years but gunshot wounds decreased by a third, and assault with hands and feet doubled. The face was more commonly injured than the neck in both years. Conclusion: Trauma to the head and neck from IPV remains a major burden to the South African health care system and to society. Minor injuries from more accessible weapons such as knives, bottles and fists significantly increased with gunshot wounds decreasing possibly due to stricter gun laws. Violence prevention programs and community education are needed to help prevent IPV.
For submission of the degree of MMED University of the Witwatersrand Johannesburg